Social Media Content and Service Delivery Empowerment in Hospitality business in Nigeria (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
AbstractThe research examines the current state of social media content and service delivery empowerment in hospitality and tourism businesses in Nigeria and it focuses on the relevance of social media as a panacea to the tourism sector. The study builds from previous studies, especially those in the areas that are related to the study. The objectives of the study were to examine if tourists find related information through a social media platform used by the tourism and hospitality business in Nigeria. It also examines if Social media empowers the customers in the choice of services offered by hospitality and tourism businesses in Nigeria and to identify if user-generated content on social media influences the quality of service offered by hospitality and tourism businesses in Nigeria. The methodology employed in this study was quantitative analysis. A Purposive or non-probability sampling technique in selecting the respondents (hospitality and tourism business in Bauchi) from the population of the study was adopted. The result obtained uncovered that online reviews is the most used social media medium which is common among all the respondents and it also revealed that there is a high relation between social media platform and the quality of services offered which indicated an influence of social media and the quality of services offered.Keyword: Social Media, Empowerment, Tourism, Hospitality, Service Delivery
Keywords: Social Media; Empowerment; Service Delivery; Tourism; Hospitality